2015
DOI: 10.1177/2042098615569726
|View full text |Cite
|
Sign up to set email alerts
|

Abuse-deterrent formulations: transitioning the pharmaceutical market to improve public health and safety

Abstract: This article evaluates abuse-deterrent formulations (ADFs) as a method to reduce prescription drug abuse while ensuring access to vital medications for individuals with legitimate need; assesses the pros and cons of ADFs and the current state of ADF adoption in the market; and develops policy recommendations to transition the market to ADFs. Although abuse-deterrent technology is still in its nascent stages, ADFs have been proven to reduce prescription drug abuse and its consequences, and even an incremental r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 14 publications
1
34
0
Order By: Relevance
“…While abuse-deterrent formulations (such as agonist-antagonist combination medications like BNX tablets and film) may have a role to play in minimising the unintended consequences associated with opioid medications [27], assessing suitability for unsupervised dosing and implementing best practice in supervised dosing remain essential strategies in protecting the integrity of OST in Australia and internationally. Despite best efforts some diversion will continue to occur, but the risks need to be weighed against the established benefits to clients and the community of supplying OST medications where needed.…”
Section: Discussionmentioning
confidence: 99%
“…While abuse-deterrent formulations (such as agonist-antagonist combination medications like BNX tablets and film) may have a role to play in minimising the unintended consequences associated with opioid medications [27], assessing suitability for unsupervised dosing and implementing best practice in supervised dosing remain essential strategies in protecting the integrity of OST in Australia and internationally. Despite best efforts some diversion will continue to occur, but the risks need to be weighed against the established benefits to clients and the community of supplying OST medications where needed.…”
Section: Discussionmentioning
confidence: 99%
“…Independent from the ER/LA REMS, other initiatives have been implemented that could decrease abuse and misuse rates, including prescription drug monitoring programs, communication campaigns aimed at increasing public and health care provider awareness of the opioid abuse epidemic, the introduction of abuse deterrent formulations (ADFs), drug take‐back programs, and others. A recent survey of primary care physicians indicated that 45% were less likely to prescribe opioids now versus the prior year . Among these initiatives, the introduction of ADFs would be expected to differentially affect the abuse and misuse of ER/LA opioid analgesics compared with the IR prescription opioids, as most ADFs released to the market have been for ER/LA opioid analgesics .…”
Section: Methodsmentioning
confidence: 99%
“…A recent survey of primary care physicians indicated that 45% were less likely to prescribe opioids now versus the prior year. 20 Among these initiatives, the introduction of ADFs would be expected to differentially affect the abuse and misuse of ER/ LA opioid analgesics compared with the IR prescription opioids, as most ADFs released to the market have been for ER/LA opioid analgesics. 21 Sensitivity analyses excluding ADFs were performed to determine the potential impact of ADF on the decrease in abuse and misuse rates.…”
Section: Methodsmentioning
confidence: 99%
“…The use of these ADF technologies was shown in clinical studies to demonstrate significant reduction in various abuse‐related parameters and indicators , as well as a decrease in intentional and unintentional overdose events . What is important to remember is that many of these studies look at abuse of a single product or two products at most.…”
Section: Practical Advantages and Limitations To Adfsmentioning
confidence: 99%